OPTIMALISASI PENAMBAHAN SERAT IJUK TERHADAP SIFAT MEKANIK PAPAN SEMEN-GIPSUM - Alimin Mahyudin; Meri Darmawi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The purpose of this research is to know the influence  addition palm fibers  on the physical and mechanical properties of composite board.  The addition of palm fiber used for each sample by comparison with gypsum and cement matrix is 0%, 2%, 4%, 6% and 8%.   The research conducted by using a type of composite laminate is a composite of two layers or more are combined into one with each of layers has its own characteristic properties, manufacturing this board used three of layers, where cement with palm fibers contain at face-back layers and gypsum with palm fibers contain at core layers.  The mechanical properties of the specimens as follows the maximum value of compressive strength and flexural strength on addition palm fibers 4% which is value 123,87 kg/cm2 and 40,83 kg/cm2.  Generally, for all research, best value for addition palm fibers on 4%.Keywords: cement-gypsum board, palm fibers, a composite laminate.